ASCILITE '97 : what works and why : proceedings of the 14th Annual Conference of the Australasian Society for Computers in Learning in Tertiary Education (ASCILITE), 8th to 10th December 1997 - Oliver, Ron, 1955-; Phillips, Rob (Robin A.); Kevill, Rod (Curtin University of Technology, 1997)
"The 1997 annual conference of the Australian Society for Computers in Learning in Tertiary Education, ASCILITE '97, will focus on the effective and efficient use of IT for teaching in the climate of reduced funding and accountability for quality teaching,including refining, reusing and repurposing. What works and why encapsulates the themes of selection, analysis and evaluation of implemented courseware by educators in the tertiary sector with a view to doing the job better." -- conference website.